The role of space assets in providing for public security - (:unkn) unknown (SPRINGER, 2008)
The new security understanding in the World has come to address a wide range of threats which can be of both man-made and natural origin. Among the threats, terrorism certainly takes center stage, in terms of short term or sudden danger. But numerous other concerns for security exist, such as overt or covert development of weapons of mass destruction, organized crime, smuggling of humans and weapons, large-scale cyber attacks, and nuclear chemical or biological accidents, which may be due to a human error or outright intentional. Then there are the natural disasters, earthquakes, hurricanes, floods, droughts, and pandemics which may be of known or as yet unknown nature. Space technology offers many tools and capabilities which prove to be quite valuable in our efforts to fight off, mitigate, compensate and provide relief for the consequences of the threats. These can be categorized briefly under three main headings, which are observation, communications and positioning information. The paper discusses how space capabilities can support our endeavor to provide security to society, in numerous situations and applications, and address the challenges and problems involved in realizing the full potential of space, including how that information needs to be integrated within a security framework.
Keywords: space technologies; public security; terrorism; natural disasters